Hidden caring, hidden carers? Exploring the experience of carers for people with long‐term conditions. (23rd February 2015) - Knowles, Sarah; Combs, Ryan; Kirk, Sue; Griffiths, May; Patel, Neesha; Sanders, Caroline
Abstract: Informal carers make a significant contribution to illness management in communities, but many struggle to access support and remain 'hidden carers'. We aimed to explore how carers of people with common long‐term conditions (LTCs, such as coronary heart disease or kidney disease) conceptualised their caring, and whether they struggled to identify themselves with the term 'carer' or access for support. We conducted semi‐structured interviews with 19 informal carers of people with LTCs recruited from local support groups. Topic guides were designed to encourage participants to provide their retrospective accounts of identifying as a carer or struggling to do so. Data were analysed using the constant comparative method. The study was designed collaboratively with a patient and public involvement (PPI) partner, and we consulted with a PPI steering group of people with lived experience of caring during the study. Results showed how participants drew on comparisons with those caring for more dependent relatives in explaining their reluctance to define themselves as a carer, and resisted adopting the label due to concerns that it would threaten the identity of the cared‐for person. The data were interpreted in terms of types of 'work' undertaken to manage LTCs, and revealed that carers of patients with LTCs appear to primarily engage in biographical and emotional support, which may be more difficult to conceptualise as legitimate caring 'work'. Participants indicated that health professionals may be in a unique position to validate their role as carers and encourage support seeking. The study suggests how the greater focus on self‐management of LTCs in the community must be complemented by recognition of this group as potentially 'hidden carers', who support the patient to minimise the impact the illness has on their lives and consequently may minimise their own caring role, with negative implications for support seeking.